3D-printed phononic crystal waveguide transducers for nonlinear ultrasonic damage detection. (July 2021) - Sherwood, Geoffrey Roger; Chronopoulos, Dimitrios; Marini, Andrea; Ciampa, Francesco
Abstract: Nonlinear ultrasonic methods typically measure second harmonic waves for a rapid and sensitive detection of material micro-cracks. However, fictitious second harmonics generated by the ultrasonic equipment can interfere with signal measurements, causing poor damage detection. This paper aims at enhancing the damage sensitivity of nonlinear ultrasound by developing acrylic phononic crystal waveguide transducers using Polyjet additive manufacturing, which can filter out undesired nonlinear harmonic waves. These sensing devices consist of traditional piezoelectric sensors surface bonded on periodically corrugated structures. Such periodicity can induce stop band frequencies in which the propagation of ultrasonic waves is inhibited. Nonlinear ultrasonic tests confirmed the filtering capabilities of phononic crystal transducers to suppress harmonics created by the ultrasonic instrumentation, thus enabling second harmonic detection on a damage aluminium plate. These results pave the way for simpler, automatable and more accurate nonlinear ultrasonic inspection systems.